Gold(I) and Gold(III) Trifluoromethyl Derivatives. Issue 43 (11th September 2013) - Martínez‐Salvador, Sonia; Falvello, Larry R.; Martín, Antonio; Menjón, Babil
Abstract Trifluoromethylation of AuCl3 by using the Me3SiCF3/CsF system in THF and in the presence of [PPh4]Br proceeds with partial reduction, yielding a mixture of [PPh4][AuI(CF3)2] (1′) and [PPh4][AuIII(CF3)4] (2′) that can be adequately separated. An efficient method for the high‐yield synthesis of 1′ is also described. The molecular geometries of the homoleptic anions [AuI(CF3)2]− and [AuIII(CF3)4]− in their salts 1′ and [NBu4][AuIII(CF3)4] (2) have been established by X‐ray diffraction methods. Compound 1′ oxidatively adds halogens, X2, furnishing [PPh4][AuIII(CF3)2X2] (X=Cl (3), Br (4), I (5)), which are assigned a trans stereochemistry. Attempts to activate CF bonds in the gold(III) derivative 2′ by reaction with Lewis acids under different conditions either failed or only gave complex mixtures. On the other hand, treatment of the gold(I) derivative 1′ with BF3⋅OEt2 under mild conditions cleanly afforded the carbonyl derivative [AuI(CF3)(CO)] (6), which can be isolated as an extremely moisture‐sensitive light yellow crystalline solid. In the solid state, each linear F3C‐Au‐CO molecule weakly interacts with three symmetry‐related neighbors yielding an extended 3D network of aurophilic interactions (Au⋅⋅⋅Au=345.9(1) pm). The high <![CDATA[$\tilde \nu $]]> <inline-graphic xlink:href="ark:/27927/pgg4t3tq4z4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO value (2194 cm−1 in the solid state and 2180 cm−1 in CH2Cl2 solution) denotes that CO is acting as a mainly σ‐donor ligand and confirms the role of the CF3 group as an electron‐withdrawing ligand in organometallic chemistry. Compound 6 can be considered as a convenient synthon of the "AuI(CF3)" fragment, as it reacts with a number of neutral ligands L, giving rise to the corresponding [AuI(CF3)(L)] compounds (L=CNtBu (7), NCMe (8), py (9), tht (10)).